(untitled) (Revista Argentina de Musicología, 2026)
This article aims to examine the poetics of contra-exilio in the work of performing artist Alberto Kurapel through an analysis of some of his essays and his discography from the 1980s, which includes the albums Contra-exilio (1982), Guerrilla (1986), and Confidencial urgent (1989). It is argued that his work undergoes a crucial shift with the emergence of the Compagnie des Arts Exilio and its conceptualization of performance theater. The analysis explores the dialogue between essay and music, and discusses key concepts in his work such as dislocation and in-between-place. It is argued that the poetics of contra-exilio crystallize in the discography through procedures of sonic friction and the expansion of vocality. Ultimately, the study examines how Kurapel’s musical work sheds light on unexplored aspects of his artistic practice and, more specifically, on his aesthetic thought. Editorial History: Received: April 7, 2026 Accepted: April 27, 2024